Inhibition of Aurora Kinase A Prevents Malignant Transformation in Oral Leukoplakia - Fengying Yin; Mengjun Li; Yi Xu; Chuan Xin; Yining Li; Qianming Chen (Journal of Oral Pathology & Medicine, 2026)
ABSTRACT Background Aurora Kinase A (AURKA), a highly conserved and potent kinase, is frequently overexpressed in diverse cancers. However, its role in the malignant transformation (MT) of oral mucosa remains poorly understood. This study investigated the expression pattern of AURKA and evaluated the therapeutic potential of its inhibitor in oral leukoplakia (OLK), the most representative oral potentially malignant disorder. Methods Immunohistochemistry was performed on clinical samples (21 normal controls, 27 OLK, 23 MT of OLK) to examine AURKA expression and its correlation with clinicopathological characteristics. The inhibitory effect of targeting AURKA on tumor proliferation was verified in vitro using two oral squamous cell carcinoma (OSCC) cell lines. Additionally, the chemopreventive effect of the AURKA inhibitor Alisertib on MT was assessed using a 4‐nitroquinoline oxide (4NQO)–induced mouse OLK model. Results AURKA expression levels positively correlated with the malignant progression of OLK. Significantly higher AURKA expression percentages were observed in non‐homogeneous lesions (10.39% ± 4.28% vs. 3.53% ± 4.22% homogeneous, p < 0.001), lesions ≥ 2 cm 2 (11.19% ± 4.55% vs. 4.69% ± 4.36% < 2 cm 2 , p < 0.01), and lesions with high‐risk dysplasia (12.10% ± 4.04% vs. 4.59% ± 4.12% low‐risk dysplasia, p < 0.001). Targeting AURKA significantly inhibited the proliferation of OSCC cells in vitro. Furthermore, Alisertib treatment effectively suppressed oral mucosa carcinogenesis in the 4NQO model. Conclusion Increased AURKA expression may represent an early molecular event in OLK carcinogenesis, and targeting AURKA with alisertib is a candidate for potential applications in the management of OLK.